Framing Analysis Of Reporting Klithih's Action In Online Media harianjogja.com - Lukman Hakim; Dwi Puspitasari (Bahasa Indonesia, 2023)
The case of crimes against humans seems to never run out of time. More and more cases of crime continue to increase. The action of klithih in Yogyakarta became one of the cases of crime that always triggered the response of many people and returned to the news in the mass media until it entered the twitter tranding topic list. For the actions committed against the victims, namely teenage children who are still in the status of this school, the community urges the authorities to crack down firmly on the perpetrators and provide protection to the surrounding residents from acts of klithih atrocities. The research used qualitative methods with the approach of framing analysis model Zhoungdang Pan Gerald M. Kosicki to find out how the framing carried out by the online media of The Harianjogja.com Newspaper in delivering news related to klithih action in Yogyakarta. The results of this study showed that the media Harianjogja.com in its reporting showed that the tendency of news to lead to the truth of klithih. Regardless of tarnishing the name of the city of Yogyakarta as a city of culture and education. Emphasis related to criminal acts that exist in the perpetrators of kithih actions becomes the source or basis of news carried out by Harianjogja.com.